Perilaku Preventif Keputihan Berdasarkan Health Promotion Model pada Remaja Putri - Dahlan, Febry Mutiariami; Suprihatin, Suprihatin; Noeraini, Vina Aresya; Aulya, Yenny (FORIKES, 2022)
Leucorrhoea can be caused by poor preventive efforts, such as an unhealthy lifestyle, poor personal hygiene, and so on. Health promotion model theory emphasizes the active role of individuals in regulating their behavior with the aim of preventing a disease, one of which is prevention of vaginal discharge. This study aims to determine the factors associated with vaginal discharge prevention behavior based on health promotion model theory in adolescent girls. This study used an analytical design with a cross-sectional design. The research was conducted at SMK Madya Depok, which involved 111 female students, who were selected using simple random sampling technique. The dependent variable in this study is vaginal discharge preventive behavior, while the independent variables are self-motivation, perceived benefits of action, interpersonal influence, and commitment to action. The research instrument is a questionnaire. The collected data were analyzed by Chi-square statistical test. The results of the analysis showed that 69.4% of respondents performed vaginal discharge preventive behavior, 73.9% of respondents had high self-motivation, 64.9% of respondents had high perceived benefits of action, 54.1% of respondents had high interpersonal influence, and 64 ,0% of respondents have a strong commitment to action. The results of the hypothesis test showed that there was a relationship between the variables of self-motivation (p=0.008), benefits of action (p=0.000), and interpersonal influence (p=0.044) with vaginal discharge preventive behavior. Meanwhile, there is no relationship between action commitment (p=0.335) and vaginal discharge prevention behavior.Keywords: prevention of vaginal discharge; adolescent girls; health promotion model ABSTRAK Keputihan dapat disebabkan oleh upaya preventif yang kurang baik, seperti pola hidup yang tidak sehat, personal hygiene yang buruk, dan sebagainya. Health promotion model theory menekankan pada peran aktif individu dalam mengatur perilakunya dengan tujuan sebagai upaya pencegahan suatu penyakit, salah satunya yaitu upaya preventif terjadinya keputihan. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan perilaku preventif keputihan berdasarkan health promotion model theory pada remaja putri. Penelitian ini menggunakan desain analitik dengan rancangan cross-sectional. Penelitian dilakukan di SMK Madya Depok, yang melibatkan 111 siswi, yang dipilih dengan teknik simple random sampling. Variabel dependen dalam penelitian ini yaitu perilaku preventif keputihan, sedangkan variabel independen yaitu motivasi diri, perceived benefits of action, pengaruh interpersonal, dan komitmen tindakan. Instrumen penelitian berupa kuisioner. Data yang terkumpul dianalisis dengan uji statistik Chi-square. Hasil analisis menunjukkan bahwa 69,4% responden melakukan perilaku preventif keputihan, 73,9% responden memiliki motivasi diri tinggi, 64,9% responden memiliki perceived benefits of action yang tinggi, 54,1% responden memiliki pengaruh interpersonal yang tinggi, dan 64,0% responden memiliki komitmen tindakan yang kuat. Hasil uji hipotesis menunjukkan bahwa ada hubungan antara variabel motivasi diri (p=0,008), manfaat tindakan (p=0,000), dan pengaruh interpersonal (p=0,044) dengan perilaku preventif keputihan. Sementara itu, tidak ada hubungan antara komitmen tindakan (p=0,335) dengan perilaku preventif keputihan.Kata kunci : pencegahan keputihan; remaja putri; health promotion model